Drug treatments for covid-19: living systematic review and network meta-analysis. (30th July 2020) - Siemieniuk, Reed AC; Bartoszko, Jessica J; Ge, Long; Zeraatkar, Dena; Izcovich, Ariel; Kum, Elena; Pardo-Hernandez, Hector; Rochwerg, Bram; Lamontagne, Francois; Han, Mi Ah; Liu, Qin; Agarwal, Arnav; et al.
Abstract: Objective: To compare the effects of treatments for coronavirus disease 2019 (covid-19). Design: Living systematic review and network meta-analysis. Data sources: WHO covid-19 database, a comprehensive multilingual source of global covid-19 literature, up to 3 December 2020 and six additional Chinese databases up to 12 November 2020. Study selection: Randomised clinical trials in which people with suspected, probable, or confirmed covid-19 were randomised to drug treatment or to standard care or placebo. Pairs of reviewers independently screened potentially eligible articles. Methods: After duplicate data abstraction, a bayesian network meta-analysis was conducted. Risk of bias of the included studies was assessed using a modification of the Cochrane risk of bias 2.0 tool, and the certainty of the evidence using the grading of recommendations assessment, development and evaluation (GRADE) approach. For each outcome, interventions were classified in groups from the most to the least beneficial or harmful following GRADE guidance. Results: 85 trials enrolling 41 669 patients met inclusion criteria as of 21 October 2020; 50 (58.8%) trials and 25 081 (60.2%) patients are new from the previous iteration; 43 (50.6%) trials evaluating treatments with at least 100 patients or 20 events met the threshold for inclusion in the analyses. Compared with standard care, corticosteroids probably reduce death (risk difference 17 fewer per 1000 patients, 95% credible interval 34 fewer to 1 more, moderate certainty), mechanical ventilation (29 fewer per 1000 patients, 54 fewer to 1 more, moderate certainty), and days free from mechanical ventilation (2.6 fewer, 0.2 fewer to 5.0 fewer, moderate certainty). The impact of remdesivir on mortality, mechanical ventilation, length of hospital stay, and duration of symptoms is uncertain, but it probably does not substantially increase adverse effects leading to drug discontinuation (0 more per 1000, 9 fewer to 40 more, moderate certainty). Azithromycin, hydroxychloroquine, lopinavir/ritonavir, interferon-beta, and tocilizumab may not reduce risk of death or have an effect on any other patient-important outcome. The certainty in effects for all other interventions was low or very low. Conclusion: Corticosteroids probably reduce mortality and mechanical ventilation in patients with covid-19 compared with standard care, whereas azithromycin, hydroxychloroquine, interferon-beta, and tocilizumab may not reduce either. Whether or not remdesivir confers any patient-important benefit remains uncertain. Systematic review registration: This review was not registered. The protocol is included as a supplement. Readers' note: This article is a living systematic review that will be updated to reflect emerging evidence. Updates may occur for up to two years from the date of original publication. This version is the second update of the original article published on 30 July 2020 ( BMJ 2020;370:m2980), and previous versions can be found as data supplements. When citing this paper please consider adding the version number and date of access for clarity.